Interferon-gamma- and lipopolysaccharide-induced tumor necrosis factor-alpha is required for nitric oxide production: tumor necrosis factor-alpha and nitric oxide are independently involved in the killing of Mycobacterium microti in interferon-gamma- and lipopolysaccharide-treated J774A.1 cells - Majumdar, S; Gupta, R; Dogra, N (Folia microbiologica, 2000)
A comparative study was done using J774A.1 and J774A.1-derived transfected cells (J774A.1 C.1) containing antisense tumor necrosis factor alpha (TNF-alpha) plasmid to determine the role of endogenous TNF-alpha on nitric oxide production as well as on the growth of Mycobacterium microti in interferon gamma (IFN-gamma)- and lipopolysaccharide (LPS)-treated cells. On stimulation with IFN-gamma and LPS a higher level of NO was observed in J774A.1 cells compared to J774A.1 C.1 which indicated that endogenous TNF-alpha is required for the production of NO. Comparing the effect of IFN-gamma and LPS on the intracellular growth of M. microti, the growth-reducing activity was higher in J774A.1 cells than in J774A.1 C.1 cells and was not completely abrogated in the presence of the nitric oxide inhibitor NG-methyl-L-arginine (L-NMA). J774A.1 C.1 cells infected with M. microti produced a significant amount of NO when exogenous TNF-alpha was added along with IFN-gamma and LPS and the concentration of intracellular bacteria decreased almost to that in IFN-gamma and LPS treated parental J774A.1 cells. Addition of exogenous TNF-alpha even in the presence of L-NMA in J774A.1 C.1 cells could also partially restore intracellular growth inhibition of M. microti caused by IFN-gamma and LPS. TNF-alpha is probably required for the production of NO in J774A.1 cells by IFN-gamma and LPS but TNF-alpha and NO are independently involved in the killing of intracellular M. microti with IFN-gamma and LPS.
Keywords: Nitric Oxide; transfekce; Cell Line; Plasmids; Colony Count, Microbial; Lipopolysaccharides; Interferon-gamma; Tumor Necrosis Factor-alpha; Transfection; lipopolysacharidy; Nitric Oxide Synthase Type II; počet mikrobiálních kolonií; mykobakteriózy; interferon gama; oxid dusnatý; Mycobacterium; Macrophage Activation; aktivace makrofágů; Animals; zvířata; Nitric Oxide Synthase; synthasa oxidu dusnatého; makrofágy; plazmidy; myši; buněčné linie; synthasa oxidu dusnatého, typ II; TNF-alfa; Mycobacterium Infections; Mice; Macrophages